PENGGUNAAN NATRIUM HIDROKSDA (NaOH) SEBAGAI ZAT ANTIKOAGULAN LATEKS (Hevea brasiliensis) - RIGUAN EPENDI EPENDI ' (Jurnal Sagu, 2015)
ABSTRACTThe aim of this research was to get the optimum concentrations of NaOH as an alternative anticoagulant oflatex. This research was conducted at Laboratory of PT. Andalas Agrolestari, Kuantan Singingi on July toDecember 2014. This research used a completely randomized design (CRD) with two steps. The first step wasto know the ability of NaOH to latex stabilities and step II was to saw the ability of format acid for latexclumed after anticoagulant came in. Data obtained were treated by the analysis of variance (ANOVA) followedby Duncan’s NewMultiple Range Test (DNMRT) the level of 5%. The results showed that optimumconcentration NaOH was addition NaOH 5%. The addition of NaOH 5% had significant effect on theanticoagulant retention time, coagulant retention time, pH, ash content, volatile substance content, Po valueand PRI value, but had not significant effect on the dry rubber content and dirt content.Key words: Anticoagulant, coagulant, latex.